Macroporosity and grain density of rubble pile asteroid (162173) Ryugu - Grott, Matthias; Biele, Jens; Michel, Patrick; Sugita, Seiji; Schröder, Stefan; Sakatani, Naoya; Neumann, Wladimir; Kameda, Shingo; Michikami, Tatsuhiro; Honda, Chikatoshi (Journal of geophysical research. Planets, 2020)
Rubble pile asteroids such as (162173) Ryugu have large bulk porosities, which are believed to result from void spaces in between the constituent boulders (macroporosity) as well as void spaces within the boulders themselves (microporosity). In general, both macroporosity and microporosity are estimated based on comparisons between the asteroid bulk density and both the bulk and grain density of meteorite analogs, and relatively large macroporosities are usually obtained. Here we use semiempirical models for the macroporosity of multicomponent mixtures to determine Ryugu's macroporosity based on the observed size-frequency distribution (SFD) of boulders on the surface. We find that Ryugu's macroporosity can be significantly smaller than usually assumed, as the observed SFD allows for an efficient packing of boulders, resulting in a macroporosity of 16% ± 3%. Therefore, we confirm that Ryugu's high bulk porosity is a direct consequence of a very large boulder microporosity. Furthermore, using estimates of boulder microporosity of around 50% as derived from in situ measurements, the average grain density in boulders is 2,848 ± 152 kg m-3, similar to values obtained for CM and the Tagish lake meteorites. Ryugu's bulk porosity corresponding to the above values is 58%. Thus, the macroporosity of rubble pile asteroids may have been systematically overestimated in the past.
Gesehen am 11.02.2021